Exploring Irish Fiddling: A Traditional Performance - Pashby, Shannon Nicole (East Carolina University, 2017)
Through earning my Minor in Music with a concentration in Violin Performance, I never encountered chances to learn traditional music. My studies were mostly focused on classical sonatas, concertos, and technique refining works including etudes, scales, and arpeggios. This research project is valuable to me, as it gave me insight into a topic that I had always been interested in, but never had the chance to perform. Each piece of music has its own background and story that shows when one plays the music. Learning, listening to, and researching the pieces composed a significant portion of my research. Finally, practicing the selected music solidified my preparation for the final project as I explored what each piece had to offer. For this research recital project, I incorporated as much of the truly traditional aspects of Irish fiddle music as is feasible. This project allowed me to explore the Celtic music genre at a deeper level. The performance required me to combine all the techniques and advice I've gained over the years in addition to the new skills I acquired as I carried out this process.
Keywords: Violin; Traditional Irish